Implementasi Tarpit Firewall untuk Optimasi Keamanan Jaringan dengan Metode NIST SP800-86 Pada Ruangan KP - Rahmat Novrianda Dasmen; ansyah, Ardi; Timur Dali Purwanto; Marlindawati (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
Network optimization is one of the important aspects that aims to improve the performance, efficiency and reliability of network systems and security on the network, but if the optimization is not carried out effectively it will pose a security threat to the network, one of the real threats is DdoS Attack, DdoS attack is a dangerous attack because this attack can paralyze the network server, Therefore, optimization needs to be carried out in the KP Room in order to avoid the threat of DdoS attacks, so the initial stage of this research will test the network to find out how optimal the network is in the KP room so that optimization is needed. The research method used is NSIT, which includes collection, examination, analysis, and reporting, the results after the research is carried out where, on the network in the kp room after testing at the examination stage and then by identifying the test results, it can be concluded that the network is not optimal enough against DdoS attacks and connection type attacks which, The optimization step taken is to apply a Tarpit firewall on the router. The implementation of Tarpit Firewall successfully overcomes DdoS attacks by slowing down incoming connections and stopping attacks, thereby improving network security from Port Scanning, DDoS, and Brute force attacks.